Thermophilic carboxydotrophs and their applications in biotechnology - Tiquia-Arashiro, Sonia M. (SpringerBriefs in Microbiology, 2014)
The book describes the products produced by carboxydotrophic bacteria and their biotechnological applications. Carbon monoxide (CO) is a widespread pollutant and a hazard to man because of its extremely toxic nature. It is a major component of some industrial gas mixtures and may be derived from coal. The carboxydotrophic bacteria obtain energy and carbon from the oxidation of CO. These organisms may be used to produce new metabolites, and the oxidases from them may be used to produce fuel cells and biosensors for CO.